Manufacturing and characterization of aerogel-polymer cores for composites - Yap, Brendan Pin Wei. (2009)
The unique structure of aerogels has enabled it to be one of the lightest material known to the mankind. Comprising of nearly 99% volume of air, it has one of the lowest density of all known materials. Although light, aerogels has a very high strength to weight ratio. Aerogels also have excellent noise and thermal insulation properties. In this project, techniques of manufacturing polymer binded aerogel cores for use in sandwich composites are examined. Polymers used are the two thermoplastics namely, Ethylene Vinyl Acetate (EVA) 3185 and Polypropylene (PP). This project aimed to examine how the different weight percentage of aerogel to polymer affects the hardness and strength of the cores. In addition Scanning Electron Microscope (SEM) was used to examine resin percolation in the cores. It was found that for PP:Aerogel cores, the Young’s modulus increases as the weight percentage of aerogel increases whereas for the EVA: Aerogel cores, the Young’s modulus increases till an optimum of 60% aerogel composition before decreasing. Signs of plastic deformation for PP: Aerogel cores appeared at 75% compressive stress while that of EVA: Aerogel cores appeared at 85% compressive stress. SEM results showed signs of resin percolation in the PP: Aerogel core samples but for the EVA: Aerogel cores, there were no obvious signs of resin percolation. This also explains the deviation in density of the PP: Aerogel cores fabricated. This project also explored the method of using PP columns filled with aerogel granules as sandwich composite cores. PP columns of 20mm and 40 mm filled and unfilled are tested for Young’s modulus and observations were made. It was discovered that Young’s modulus is lower for columns filled with aerogel as compared to unfilled columns. Interesting observations were made with regards to the compressive behaviour of the columnar structures and the structure of compacted aerogels.